Estimating unsaturated hydraulic conductivity function of sodic and normal soils using point source field dripper method - OJHA, ROHIT PRATAP; VERMA, CHHEDI LAL; DENIS, D. M. (Journal of Soil and Water Conservation, 2018)
In the present study saturated hydraulic conductivity and relative measure of gravity over capillarity were estimated using saturated front radii of short duration tests and compared with the values estimated with extrapolated saturated front radii. It has been observed that for small dripper discharges, steady state flow condition is established after a long time. Use of short duration test data may results in erroneous estimates of hydraulic conductivity. In the present study extrapolation of saturated wetted front radii by the best fitting models was proposed for estimation of unsaturated hydraulic conductivity and relative measure of gravity over capillarity using Wooding and Warrick models. The saturated hydraulic conductivity values obtained with extrapolated saturated front radii using Wooding model were 56.83, 55.34, 75.70 and 7.25% lower and by using Warrick model 31.12, 66.11, 45.70 and 3.31% lower in cultivated recently tilled normal soil, cultivated untilled normal soil, cultivated recently tilled sodic soil and uncultivated untilled sodic soil, respectively. A combination of short duration test with best fitting extrapolation model is recommended for field application for reliable estimates of saturated hydraulic conductivity and relative measure of gravity over capillarity avoiding long duration field tests. The best fitting extrapolation model could save time and provide reliable estimates unsaturated hydraulic conductivity function.